Juridical Review of the Food and Drug Administration Sales of Expired Food Stocks in Modern Markets Medan City - Sunarto, Atika; Sitompul, Aryo; Aruan, Anri Penataran; Kaur, Pawiter Dinsha; Adnan, Muhammad Ali (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Food is a basic human need, and food safety is a consumer right protected by law. The circulation of expired food, including in Medan's modern markets, is a serious concern due to its impact on health. This research uses a descriptive-contextual qualitative method and highlights three important points. This research aims to analyze the legal efforts of the Food and Drug Supervisory Agency (BPOM) in handling the sale of expired food in Medan's modern markets. BPOM has the authority to regulate, supervise, and take action against violations related to food safety. Relevant legal arrangements include the Consumer Protection Law and the Food Law. Businesses that sell expired food may be subject to administrative and criminal sanctions. BPOM conducts preventive efforts such as education and routine supervision, as well as repressive efforts in the form of confiscation, administrative sanctions, and criminal prosecution through cooperation with the police. This study concludes that the role of BPOM is very important in protecting consumers from the dangers of expired food, but synergy between law enforcement, business coaching, and increasing consumer awareness is needed to make consumer protection efforts more effective.